Bridging visible and telecom wavelengths with a single-mode broadband photon pair source - Soeller, C; Brecht, B; Mosley, P; Zang, L; Podlipensky, A; Joly, N; Russell, P; Silberhorn, C (2010)
We present a spectrally decorrelated photon pair source bridging the visible and telecom wavelength regions. Tailored design and fabrication of a solid-core photonic crystal fiber (PCF) lead to the emission of signal and idler photons into only a single spectral and spatial mode. Thus no narrowband filtering is necessary and the heralded generation of pure photon number states in ultrafast wave packets at telecom wavelengths becomes possible. © 2010 The American Physical Society.